"Feeling part of a team" a mixed method evaluation of a dedicated education unit pilot programme. (September 2018) - Crawford, Ruth; Jasonsmith, Adelaide; Leuchars, Deborah; Naidu, Anjana; Pool, Leanne; Tosswill, Laura; Trezise, Kathy; Wordsworth, Alexandra
Abstract: The clinical learning environment is integral to the sustainability of the nursing workforce. Traditionally undergraduate nursing students were preceptored one-to-one with a registered nurse. With an increasingly complex clinical environment and more RNs working part-time, that model has become problematic. The Dedicated Education Unit (DEU) is a model of student learning whereby students are nurtured by all staff in a clinical area, clinical and academic staff collectively support the student and student learning is a collaborative process. In this study, a pilot DEU model in three clinical areas of one District Health Board in New Zealand was evaluated. These DEU are different from others reported in the literature as three unique nursing programmes from two Tertiary education providers (TEPs) in an urban area in New Zealand were involved in the pilot. The approach in this study was a mixed method descriptive evaluation design, undertaken in two phases: phase one was an online anonymous survey completed by 42 nurses and nurse managers employed in three DEUs and 24 undergraduate third year nursing students who were completing their final nine week pre-graduate placement. Phase two was six separate focus groups with registered nurses and undergraduate nursing students. Students (91%) and staff (85%) were satisfied with their participation in the DEU. Students described feeling part of the health care team and staff reported enjoying working with students from different programmes, also noting the supportive DEU structure gave them more opportunity to engage with student learning. Role clarification was an issue which needs to be resolved. Staff from three units at a District Health Board and three unique nursing programmes were able to develop learning partnerships, collaborating together to provide a positive, nurturing learning environment for nursing students and a clinical setting where nurses enjoyed their teaching/coaching roles. Highlights: Health providers, academics and students take shared responsibility for student learning in clinical placements The CLN is the 'go to' person for students 75% of students feel part of a team in the DEU